(untitled) (Studia Prawnicze / The Legal Studies, 2010)
Redukcja utrzymująca skuteczność jest jedynym ze sposobów ograniczenia zastosowania sankcji nieważności bezwzględnej. Jedną z odmian tzw. częściowej nieważności czynności prawnej, o której mowa w art. 58 § 3 k.c., a zatem instytucją prawną skierowaną na zachowanie w mocy umowy. Zastosowanie redukcji dotyczy sytuacji, gdy dana część czynności prawnej (np. klauzula umowna) jednocześnie obejmuje treść dozwoloną i niedozwoloną. W przypadku wady całej klauzuli w grę wchodzi spór o ważność całej czynności prawnej. Jeżeli cześć klauzuli jest wadliwa, wówczas na pierwszym miejscu istotna jest ocena ważności pojedynczej klauzuli. Dopiero po ustaleniu jej nieważności późniejsze zastosowanie przesłanek w stosowaniu tzw. częściowej nieważności mogłoby zagrozić prawnemu bytowi całej czynności prawnej. The article discusses the concept of the so-called “reducing upholding enforcement” (validity) of juridical acts in the light of the draft of Book One of the new Polish civil code (published in 2008). The draft contained a dedicated legal basis allowing courts to reduce the terms (i.e. contractual rights or obligations) of a contract which is invalid – it is so called “reducing upholding effectiveness”. In the article an analysis has been carried out of the most important theoretical and practical backgrounds. The main concern is about the scope of the judge’s power to reduce or even revise the term of the juridical act (contract) and its limit. The comparative context of reduction has also been presented. Reduction is one of the ways to avoid nullity of the juridical act, especially contract clause and is one form of partial invalidity. The main function of it is to protect parties from the disadvantageous and sometimes unexpected effects of invalidity, especially those effects for a party protected by the sanction of nullity (“weaker party”). Reducing the scope of the void term leads to the legal effects of a juridical act remaining in force to the extent allowed and valid in the realm of private law (for instance to cut out the part infringing mandatory rules). This paper includes also comparative remarks on the admissibility of such a reduction in chosen legal systems ius civile and common law tradition. Amongst ius civile systems the doctrine of reduction is widely accepted in German law (called Geltungserhaltende Reduktion). In the common law tradition, reduction is rather inadmissible as a principle. There is a restrictive approach for partial invalidity within the doctrine of severance in contract law. Even though the severability of the contract is only partly invalid, it is widely recognised that reducing invalid contractual terms is hard to accept because of the blue pencil rule and prohibition of such interventions in contractual matters. The article discusses exceptions which can be found in some countries (especially New Zealand or Québec law on illegal contracts). The fundamental problem arising in the area of reducing upholding effectiveness is connected with the fine line between reducing the scope of a void term as a part of the juridical act and revising the matter hidden behind the invalid part of the juridical act. In other words, with the limitations of the courts’ discretion in rewriting an invalid clause. Effects which are intended by reducing the scope of a void term can be achieved in other legal ways. The main alternative is the concept where the sanction of invalidity is established by the judge – in a structured discretion form - which was proposed in the model rules of The Principles of European Contract Law and Draft Common Frame of Reference. That approach reveals some aspects of a structured discretion useful to propose some amendments for the Polish normative basis of reduction. These are statutory factors which are supposed to be taken into consideration when a court exercises its power to sever, reduce or revise an invalid clause or obligation. One basic factor should prevent the so called innocent party from suffering injustice flowing from making a part of a juridical act null and void. This could be done by refusing partial invalidity and instead reducing or revising the invalid part (especially contract term). A version of a legal ground presented by the draft of Book One of the new Polish civil code to reduce the scope of the juridical act clause should be accepted as a step forward in the promotion of justice and efficiency of private law regulations. Implementation of that legal doctrine is supposed to be more detailed and include some aspects of structured discretion i.e. factors limiting the courts’ power to reduce or revise a void clause.